Association of independent dietary antioxidant intake, and CDAI level with risks of all-cause and cardiovascular-cause death among population with cardiovascular disease - Xintao Hu; Zhao Zhao; Qian An; Yang Li; Bing Wang (BMC Public Health)
Abstract Background Antioxidants have been investigated for their potential to prevent cardiovascular disease (CVD); however, their association with mortality risk in patients with CVD has not been thoroughly evaluated. The aim of this study was to assess the relationship between individual antioxidants and the composite dietary antioxidant index (CDAI) with the risk of death in patients with CVD. Methods This study included 1,395 participants with CVD from the National Health and Nutrition Examination Survey (2001–2010). Cox proportional hazards models were employed to estimate the hazard ratios (HRs) and 95% confidence intervals （CIs） for individual antioxidants (including vitamins A, vitamins C, vitamins E, selenium, carotenoids and zinc) and CDAI levels in relation to all-cause mortality and cardiovascular death. Additionally, restricted cubic splines (RCS) were utilized to further investigate potential nonlinear relationships. Results Individual antioxidants, including vitamin C and vitamin E, were inversely associated with both all-cause and CVD-cause mortality in patients with CVD. As for CDAI, compared to participants in the first tertile(T1) of CDAI, the fully adjusted HR for all-cause mortality in the third tertile (T3) was 0.62 (95% CI: 0.46, 0.85). For CVD mortality, individuals with T3 of CDAI also exhibited a significantly reduced risk, with an HR of 0. 58 (95% CI: 0. 35,0.97). RCS analysis revealed a linear relationship between CDAI and all-cause mortality, while a non-linear, inverted L-shaped relationship was observed for CVD mortality. Conclusion Higher levels of dietary antioxidants are associated with a reduced risk of both all-cause and cardiovascular-cause mortality in patients with CVD. These findings suggest that increasing antioxidant intake may serve as a potential strategy for improving outcomes in this population.